Studies on Dehumidified Refrigerated Storage of Groundnut Seeds - Rayaguru, Kalpana; Bebartta, J P (Journal of Agricultural Engineering, 2008)
Groundrut (Arachis hypogaea) is one of the major potential sources of edible oil in Orissa because of its yield economics. But the unavailability of seeds stands as a major constmint for extensive coverage. This problem can be solved only if groundnut seeds, which are harvested at the end of May, are preserved, so that seeds can be made available to the farmers at the right time during October sowing without losing the available residual moisture. This becomes significant during the period from June to November due to prevailing high temperature and high relative humidity. Storage experiments were carried out to store groundnut seeds under dehumidified refrigerated storage conditions of temperature 15 to 25±1degree C and relative humidity 60 to 80±2%. During storage of seeds the prevailing atmospheric temperature and relative humidity were recorded regularly. Performance of the storage system was evaluated at one month interval through the standard tests for moisture content, germination percentage, viability percentage and seed health. Analysis of observations on seeds stored under different conditions for a period of one year has been made. The, seed quality of the samples was comparable at 15degree and 20degree C with 60% RH. The samples stored at 80% RH irrespective of temperature deteriorated significantly after four months of storage. Similarly the samples stored under ambient condition showed highly unacceptable seed qualities with higher infection percentage after two months of storage. It is evident that the selection of storage conditions will depend on both quality and economic considerations of the end user.